Conclusion: integrating ecology and poverty reduction - Ingram, J.C.; DeClerck, Fabrice A.J.; Rumbaitis del Rio, Cristina (Springer, 2012)
As discussed throughout the chapters of the two volumes comprising this series on Integrating Ecology and Poverty Reduction, in recent years an increasing amount of global attention has focused on the role of the natural environment in contributing to poverty reduction (McNeely and Scherr 2003; Ash and Jenkins 2007; World Bank 2007; Tekelenburg et al. 2009; Chivian and Bernstein 2008; Galizzi and Herklotz 2008). These volumes complement and build upon this growing body of work, but look specifically at the ecological dimensions of multiple development challenges related to rural poverty and the ways in which ecological science can be applied to address some of these challenges.